How Marketing Mix of Grab Affects Customer Loyalty - L. Rananda Bintara Chandra (iBuss Management, 2020)
Online transportation service company Grab has distributed Rp 9.9 trillion (US$720.72 million) in earnings to its drivers and its micro, small and medium enterprise (MSME) partners annually. According to Astutik (2018), Grab is contributing 8,9 trillion worth of income in Surabaya only. Thus, the researcher wants to focus on marketing mix variables that affect customer loyalty of Grab car and bike mediated by customer satisfaction. This research is quantitative analysis research, and the research methodology conducted by using survey of self-administered questionnaire from primary sources of at least 114 people between 18 to 38 years old. To execute the research, the simple random sampling method will be applied. The researcher will distribute questionnaire to respondents who know about Grab and ever use the service, and the data is being analyzed using multiple regression with mediating variable. This research has proved that price affects customer loyalty mediated by customer satisfaction. Keywords: Customer Satisfaction, Marketing Mix, Online Transport, Customer Loyalty, Ride-hailing Industry